1995
DOI: 10.1152/ajplung.1995.269.2.l171
|View full text |Cite
|
Sign up to set email alerts
|

Collagen is a survival factor against LPS-induced apoptosis in cultured sheep pulmonary artery endothelial cells

Abstract: Lipopolysaccharide (LPS) causes direct pulmonary endothelial injury that can precipitate cell death. We investigated the ability of LPS to produce apoptosis in sheep pulmonary artery endothelial cells (SPAEC) grown in monolayer on plastic or collagen. When SPAEC were grown on plastic, LPS (100 ng/ml) caused internucleosomal DNA fragmentation (IDF) to 180- to 200-base pair ladders after 4 h. Higher-order chromatin damage, producing 50-kilobase DNA fragments, occurred within 2 h. Significant DNA strand breaks we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 0 publications
1
42
0
Order By: Relevance
“…This system also allows us to Similar to our ®ndings for myeloma cells, Sethi et al (1999) recently reported that binding of small cell lung cancer cell lines to FN via b1 integrins conferred resistance to DNA damaging drugs. Furthermore Hoyt et al (1996) demonstrated that adhesion to ®bronectin protected tumor-derived endothelial cells from VP-16 induced double-strand breaks suggesting that adhesion could also protect cells responsible for the vascularization of the tumor. Collectively, these data indicate that b1 integrins may represent a cell surface pathway capable of protecting cells from drug induced cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…This system also allows us to Similar to our ®ndings for myeloma cells, Sethi et al (1999) recently reported that binding of small cell lung cancer cell lines to FN via b1 integrins conferred resistance to DNA damaging drugs. Furthermore Hoyt et al (1996) demonstrated that adhesion to ®bronectin protected tumor-derived endothelial cells from VP-16 induced double-strand breaks suggesting that adhesion could also protect cells responsible for the vascularization of the tumor. Collectively, these data indicate that b1 integrins may represent a cell surface pathway capable of protecting cells from drug induced cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also clear that LPS has direct effects on the endothelium (53)(54)(55)(56)(57). As with TNF, in most studies LPS does not induce significant death of human endothelial cells unless new gene expression is blocked (3,6).…”
Section: Discussionmentioning
confidence: 99%
“…Presumably, fibronectin adhesion reduced the availability of topo IIb for forming drug-induced cleavable complexes. Similarly, Hoyt et al (1996) also demonstrated that activation of b1 integrins in tumor derived endothelial cells or lung endothelial cells resulted in a decrease in etoposide-and bleomycininduced DNA damage (Jones et al, 2001). Moreover, in the cell spheroid model resistance associated with topoisomerase II inhibitors also correlated with a decrease in DNA damage compared to cells grown as a monolayer (Oloumi et al, 2000).…”
Section: Effects Of Adhesion On Drug-induced Dna Damagementioning
confidence: 94%